Characteristics of sleep-conducive music: A narrative evidence review - Wang, Yuluan; Rivard, Annette; Guptill, Christine; Boliek, Carol; Brown, Cary (Advances in Social Sciences Research Journal, 2020)
Objectives: Sleep deficiency (SD) is a prevalent problem and has serious negative consequences for physical, cognitive, and psychological well-being. The use of music as a non-pharmacological sleep intervention has been proposed in several studies. A 2014 meta-analysis of 10 randomized trials evaluating the impact of music on sleep concluded that it can decrease sleep onset delay (latency) and sleep disturbances, increases sleep duration, and improves daytime dysfunction. It appears that, to-date, evidence-based guidelines for the selection and/or production of sleep-promoting music do not exist. This review addresses that gap and synthesizes available literature towards the goal of developing guidelines grounded in the evidence-based characteristics of sleep conducive music. Design and Results: A narrative review of research papers relevant to the topic identified evidence-based characteristics of sleep-conducive music related to tempo, rhythm, pitch, volume, and duration. Conclusion: This identification and compilation of evidence-based characteristics of sleep-conducive music can underpin future research that targets development and testing of specific music to promote sleep.